The effectiveness of exercises in patients with thumb carpometacarpal osteoarthritis: a study protocol for a systematic review and meta-analysis - Karanasios, Stefanos; Mertyri, Dimitra; Karydis, Fotis (International Journal of Clinical Trials, 2023)
Background: The thumb carpometacarpal osteoarthritis (CMC-OA) is a common musculoskeletal condition of the hand causing increased pain and significant disability. Although different modes of exercises are usually prescribed during the management of the condition, the evidence for their effectiveness is sparse. The aim of this protocol is to investigate through a systematic review the effectiveness of exercises compared with other non-surgical interventions in reducing pain and improving function in the management of the thumb CMC-OA. Methods: We will conduct this systematic review following the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines. PubMed, CINAHL, EMBASE, PEDro, ScienceDirect, Cochrane Library, Grey literature databases and clinical trial registries will be searched. Two reviewers will independently evaluate the retrieved results. Subsequently, data extraction of the eligible trials will be conducted by two independent researchers. We will use the grading of recommendations assessment, development, and evaluation (GRADE) approach to assess the certainty of evidence. Conclusions: This systematic review will provide evidence for the clinical benefits of exercises compared with other conservative interventions in the management of patients with thumb CMC-OA. Trial registration: PROSPERO registration number is CRD42023461505.